Suitability of CPOT and BPS to Assess Pain Response in Intubated Mohammad Hoesin Hospital Intensive Care Patients - Dwi Darmanto; Agustina Br Haloho; Rizal Zainal; Erial Bahar (Journal of Anesthesiology and Clinical Research, 2020)
Background. Assessing pain in mechanically ventilated patients is an important thing for leads to improved outcome and better quality life of patients in the ICU. CPOT and BPS has been developed for measuring nonverbal patients. Aims. To validate suitability the use of CPOT and BPS in ICU RSMH. Methods. Observational analytic with cross sectional design was chosen for 50 samples conducted on July 2020 in ICU RSMH. Data was collected before and after pain procedure. Result. From 50 patients mostly 27(54%) male with age majority > 30 years old 39 (78%). The lowest GCS 2 and the highest 10. Length of treatment in ICU was 1 – 20 days. Bleeding variations was 0 - 1200 cc. BPS average before painful procedure was 2 – 5 and after panful procedure was 5 – 7. CPOT average before painful procedure was 1 – 6 and after painful procedure was 3 - 8. Kappa before painful procedure are moderate (kappa=0,435) and after painful procedure are fair (kappa=0,248) with strongly correlated in Pearson correlation (r = 0,644, r = 0,610) (p < 0,05). Conclusion. This study demonstrated that CPOT more detail than BPS for measuring pain in intubated patients.